ANALISIS YURIDIS PENJATUHAN PIDANA TERHADAP PELAKU TINDAK PIDANA KEKERASAN DALAM RUMAH TANGGA ( Studi Kasus Putusan Nomor:227/Pid.Sus/2021/PN Kpg) - Diaz, Maria Selviana; Wilhelmus, Bhisa Vitus; Manuain, Orpa Ganefo (Petitum Law Journal, 2025)
This research aims to analyze the imposition of criminal law in deciding criminal cases againts perpetrators of domestic violence in Decision No: 227/Pid.Sus/2021/PN Kpg. The type of research used is normative research with a Literature study that collects legal materials such as laws and regulations, case decitions, and non-legal materials such as books and the internet. The primary, secondary, and tertiary legal data sources are used . Based on the research results, the sentence imposed in Decision no: 227/Pid.Sus/2021/PN Kpg is considered light and does not match the impact caused by the perpetrators actions, which resulted in the victim suffering injuries.